2022
DOI: 10.1039/d1cp04110j
|View full text |Cite
|
Sign up to set email alerts
|

Matrix effects on hydrogen bonding and proton transfer in fluoropyridine – HCl complexes

Abstract: We report an extensive computational and spectroscopic study of several fluoropyridine–HCl complexes, and the parent, pyridine-HCl system. Matrix-IR spectra for pentafluoropyridine–HCl, 2,6-difluororpyridine–HCl, and 3,5-difluororpyridine–HCl in solid neon exhibit shifts for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, the substitution position of the F‐functional group has a significant effect on the acidity of aromatic compounds, and the meta‐position substitution is more favorable for the basicity enhancement than the ortho‐position substitution, making m‐tfpe more easily to react with protons. [ 17 ] Besides, the calculated electron cloud density on pyridine groups of LUMO in HOF‐FJU‐40H is increased compared to HOF‐FJU‐40, which is ascribed to the protonated nitrogen atom that enhances the electron‐withstanding ability (Figure S28, Supporting Information). And, the calculated HOMO–LUMO energy gap decreases from HOF‐FJU‐40 to HOF‐FJU‐40H, which confirms that the protonation narrows the HOMO–LUMO energy gap, compatible with the redshifted change on emission fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the substitution position of the F‐functional group has a significant effect on the acidity of aromatic compounds, and the meta‐position substitution is more favorable for the basicity enhancement than the ortho‐position substitution, making m‐tfpe more easily to react with protons. [ 17 ] Besides, the calculated electron cloud density on pyridine groups of LUMO in HOF‐FJU‐40H is increased compared to HOF‐FJU‐40, which is ascribed to the protonated nitrogen atom that enhances the electron‐withstanding ability (Figure S28, Supporting Information). And, the calculated HOMO–LUMO energy gap decreases from HOF‐FJU‐40 to HOF‐FJU‐40H, which confirms that the protonation narrows the HOMO–LUMO energy gap, compatible with the redshifted change on emission fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Here, too, the study of isolated ions has been difficult. Instead, hydrogen bonding with simple Lewis acids has been used by many researchers as a proxy for protonation, since spectroscopic shifts of the hydrogen stretching motion of the acid have been correlated with the proton affinity of the base. To this end, Lokshin and co-workers studied the hydrogen-bonded complexes of ferrocene and its alkyl derivatives with (CF 3 ) 3 COH in liquid xenon in the range of 165–270 K and concluded that the hydrogen bonding was to the cp ring of ferrocene. However, this conclusion was based solely on analogy to olefin complexes and was made without the benefit of computational chemistry (which was not available at the time).…”
Section: Introductionmentioning
confidence: 99%